Measurement of the direct CP violating charge asymmetry in B± →μ±νμD0 decays - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2017)
We present the first measurement of the CP violating charge asymmetry in B±→μ±νμD0 decays using the full Run II integrated luminosity of 10.4 fb-1 in proton-antiproton collisions collected with the D0 detector at the Fermilab Tevatron Collider. We measure a difference in the yield of B- and B+ mesons in these decays by fitting the reconstructed invariant mass distributions. This results in an asymmetry of AμD0=[-0.14±0.20]%, which is consistent with standard model predictions.